中华传统宗教信仰在东南亚的蜕变：新加坡的道教和佛教研究 = Transformation of traditional Chinese religious beliefs in South-East Asian society : a case study of Taoism and Buddhism in Singapore - 许原泰 Hue Guan Thye (2011)
通过追溯中华传统宗教信仰在新加坡河畔登陆和发展至今的过程，本文着重研究道教和佛教在新加坡的传播沿革和模式，是为从侧面来了解狮城华社更迭变迁之微观途径。同时，本文也结合了历史观和社会观的双重视野，详细描述和分析狮城道教和狮城佛教在不同时代背景下所展开的各类社会活动，并从国家的土地规划政策和空间合并与分裂等课题，评估塑造中华传统宗教信仰在现代都市国家不断蜕变的多重力量。本文共计九章。第一章概述这项研究的主旨、范围和方法，确立本文之思考方向。第二章按照前人的学术研究，为儒、释、道三教信仰归纳出基本定义，以及按照新加坡的实际情况，分析何谓新加坡的佛教、道教、儒教信仰，俾为本论文的研究对象划分出最贴近新加坡传统华族宗教实况的范围。第三章至第六章是本论文的核心部分，主要是追溯和归纳道教和佛教在新加坡的发展过程和传播模式。第三章和第四章是探讨道教在新加坡的发展轨迹和演变过程，着重分析和比较民间宗教信仰与传统道教信仰在新加坡的微妙博弈。第五章和第六章是探讨汉传佛教在 15 世纪前的新加坡之传播可能，以及归纳出北传佛教在新加坡发展的不同阶段。第七章是从宗教信仰和世俗政治互相碰撞的角度，分析新加坡华族庙宇在城市重建计划中为了继续求存而不得不再三转型之严峻考验。第八章则结合上述篇章，深入探讨道教和佛教在新加坡的内在结构和影响层面，分析两者的发展前景和多重挑战。最后一是本论文的扼要总结，从这项研究课题中审视传自中国的佛教和道教是如何对新加坡华社的发展做出回应，并从中提炼出一得之见，概括新加坡多元城市社会对中华宗教文化的回馈和贡献。由于过去几乎没有专家学者在这方面做过专业性的深入研究和对照，因此，本论文通过大量收集历史文献和结合每个时代的传播特点来还原历史面貌，便显示着其刻不容缓的迫切性。这是本论文的独特贡献，也是价值所在。This thesis details the development of traditional Chinese religious beliefs in Singapore by tracing their early growth on the banks of the Singapore River to their present structure. It focuses on the propagation and evolution patterns of the Singapore Taoism and Buddhism, whose metamorphosis is a microcosm of the overall transformation of the Singapore Chinese community. Through a historical and sociological descriptive analysis of change in both religious social activities, as well as the resulting spatial aspects and the influence of the state land policy, it also evaluates the forces that have shaped traditional Chinese religious beliefs in this modern city-state. This thesis consists of nine chapters. The first chapter outlines the direction of the whole thesis; it highlights the motivation, introduces the general background, lays out the framework, and raises some perceptive questions. The second chapter is devoted to the general religious background of the region and the history of the three mainstream Chinese religions; it provides a fertile ground for the following chapters. Chapter three to six are the central chapters of the thesis. The third and fourth chapters compare the differing impacts of Fork Religious Beliefs and Traditional Taoist Beliefs on the historical development and patterns of propagation of Taoism. Chapter five and chapter six discuss the possibility of Singapore being an ancient Buddhist country prior to the 15th century, as well as the different propagation stages of Mahayana Buddhism in Singapore. Chapter seven highlights the predicament facing the propagation of the traditional Chinese Temple in Singapore and analyses how these Temples have accommodated to the utilization of space demands arising from the Urban Redevelop Programme and they have been transformed in their quest for survival in this city. Chapter eight links the previous chapters and dwells on the structure and development of both Singapore Taoism and Buddhism; it objectively presents the advantages and challenges faced by both religions and poses valuable question to be pondered. The final chapter provides a succinct sum-up of the whole thesis, demonstrating that this field work has brought the study of the Chinese religions of Singapore to a higher level. In sum, this thesis highlights the pattern of Taoist and Buddhist propagation in Singapore (before and after independence) and analyses their culture and belief structure in Singapore. As such a detailed study has not been done before, this study strives to fill this gap and make a valuable contribution to society towards a better understanding of Singapore’s Traditional Chinese religious culture and practices.